Belgium : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
The Belgian economy showed considerable progress through 2011 in terms of both growth and employment. However, the 2013 Article IV Consultation underlines that the European recession has had a negative impact on its economy, giving rise to unemployment. The economy has entered its second year of near zero growth. To help restore competitiveness and improve financial market conditions, decisive actions have been taken. Important decisions in 2012 include pension schemes and unemployment benefit systems with the objective of raising the employment rate to 73 percent by 2020.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet